Adolescent Usage of Wattpad: Reading Habit or Digital Addiction? - Kurt, Berker; Yıldız, Ümit; Hancı‐Azizoğlu, Başak Eda; Vural, Ersen; Kafes, Hüseyin (Psychology in the schools, 2025)
ABSTRACT One of the gifts of the Digital Age in the field of literacy is Wattpad, a digital social reading application. The Wattpad platform is the world's largest reading network, with millions of users and diverse content. Within this context of significance and relevance, this study aims to reveal the interactions of adolescents using Wattpad, their reading habits, and their digital addiction, as well as to make relational comparisons among these factors. Data for the study were collected from 379 adolescents using a quantitative survey design, employing three instruments: the Wattpad Usage Questionnaire, the Reading Habit Inventory, and the Digital Addiction Scale. The quantitative analysis of the findings indicates that adolescents exhibit varying levels of reading habits and digital addiction. A low‐level negative correlation between reading habits and digital addiction was identified, suggesting that as reading habits increase, digital addiction tends to decrease. Notably, the most significant result of this study is that social interaction with peers, rather than reading habits or digital usage, is the primary factor influencing adolescents' Wattpad use. Moreover, it appears that Wattpad use has not yet been fully embraced by formal educational institutions. This study enhances our understanding of adolescents' use of Wattpad and offers pedagogical insights for stakeholders, along with significant implications for future research. The implications of this study extend beyond academic circles, calling for parents, educators, and policymakers to collaboratively foster environments that support healthy digital reading practices, thereby promoting balanced literacy development among adolescents. Summary Educators and parents should encourage structured peer discussions around popular Wattpad content to improve literacy and foster critical thinking, using the platform's social aspect as a learning tool. To reduce digital addiction, practitioners should advocate for balanced reading practices that combine traditional texts with digital texts, providing guidelines for healthy digital consumption among adolescents. Schools should consider including Wattpad in their curricula by assigning critical analyses or creative writing tasks based on its content, recognizing digital reading as a valuable educational resource.